Basic business mathematics - Don, Eugene; Lerner, Joel (New York : McGraw-Hill, 2000)
Mathematics and Statistics
Keywords: Business mathematics; Arithmetic; Payroll; Depreciation; Interest; Discount; Stocks; Bonds; Buying; Selling; insurence; Statistics